2005
DOI: 10.1074/jbc.m411865200
|View full text |Cite
|
Sign up to set email alerts
|

The Mammalian Target of Rapamycin-p70 Ribosomal S6 Kinase but Not Phosphatidylinositol 3-Kinase-Akt Signaling Is Responsible for Fibroblast Growth Factor-9-induced Cell Proliferation

Abstract: Fibroblast growth factor-9 (FGF9) is a potent mitogen that stimulates normal and cancer cell proliferation though the signaling mechanism is not fully understood. In this study, we aimed to unravel the signaling cascades mediate FGF9 actions in human uterine endometrial stromal cell. Our results demonstrate that the mitogenic effect of FGF9 is transduced via two parallel but additive signaling pathways involving mammalian target of rapamycin (mTOR) and extracellular signal-regulated kinase. Activation of mTOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…For instance, FGF-9 could induce a PLC-g1-controlled mTOR and p70S6-kinase activation, although PI3K and Akt were not at all activated in the analyzed human endometrial stroma cells (Wing et al, 2005). Two other examples of Aktindependent mTOR/p70S6-kinase activation are provided from transformed B lymphocytes (Wlodarski et al, 2005) and from prostaglandin-F2a-treated bovine luteal cells (Arvisais et al, 2006), even though the mechanisms involved here might be different.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, FGF-9 could induce a PLC-g1-controlled mTOR and p70S6-kinase activation, although PI3K and Akt were not at all activated in the analyzed human endometrial stroma cells (Wing et al, 2005). Two other examples of Aktindependent mTOR/p70S6-kinase activation are provided from transformed B lymphocytes (Wlodarski et al, 2005) and from prostaglandin-F2a-treated bovine luteal cells (Arvisais et al, 2006), even though the mechanisms involved here might be different.…”
Section: Discussionmentioning
confidence: 92%
“…For example, it has been recently shown that prostaglandin F 2a activates mTOR via MAPK, but not via AKT in luteal cells (18), whereas mTOR activation, independent of both AKT and MAPK, has been detected in B lymphocytes (19) and endometrial stromal cells (20). The dissection of the specific mechanisms involved in the TSH-dependent activation of mTOR is tightly linked to the identification of the key players downstream of TSHR, and those upstream of mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…38 Activation of p70S6K can occur by dual activation of an mTOR-dependent pathway targeting Thr389 and an ERK1/2-dependent pathway targeting Thr421/Ser424, both of which are independent of the Akt/PKB pathway. 32,33 Further evidence in support of ILK-dependent activation of p70S6K was the finding in isolated cardiomyocytes of increased ILK-specific phosphorylation of S6 ribosomal protein, which is a downstream target of p70S6K. Our results extend the recent finding that the tripartite complex of ILK and the cytoskeletal interacting proteins particularly interesting new cysteine-histidine-rich protein and ␣-parvin is necessary for phenylalanine-induced hypertrophy in neonatal rat cardiomyocytes 39 and are consistent with the physiological hypertrophic response and augmented cardiac function associated with genetic stimulation of the ERK1/2 branch of the mitogen-activated protein kinase signaling pathway.…”
Section: Ilk-induced Hypertrophy Features Activation Of Rac1 and P70s6kmentioning
confidence: 99%
“…Adenoviral overexpression of wild-type ILK, but not the ILK R211A mutant construct or GFP control, caused activation of p70S6K at Ser371 and Thr389, which was prevented by the small-molecule ILK inhibitor KP307-2 26 ( Figure 6C). Because Thr421 and Ser424 are targets of ERK1/2, 33 we tested whether phosphorylation at these sites was ILK dependent. In concordance with the findings in the Tg mouse hearts (supplementary Figure IIIc and IIId) and human hypertrophic hearts ( Figure 3C), our results indicate that acute ILK upregulation in human fetal cardiomyocytes in vitro also induces KP307-2-inhibitable phosphorylation of p70S6K; specifically, ILK activation resulted in an increased intensity of phospho-Thr421/Ser424 and phospho-Thr389 of p70S6K, indicating cooperative regulation by ERK1/2 and mTOR kinases, respectively ( Figure 6C).…”
Section: Ilk Activates the P70s6k Pathway In Isolated Human Cardiomyomentioning
confidence: 99%